Gambling and Impulsivity Traits: A Recipe for Criminal Behavior? - Mestre-Bach, Gemma; Steward, Trevor; Granero, Roser; Fernández-Aranda, Fernando; Talón-Navarro, María Teresa; Cuquerella, Àngel; Baño, Marta; Moragas, Laura; del Pino-Gutiérrez, Amparo; Aymamí, Neus; Gómez-Peña, Mónica; Mallorquí-Bagué, Núria; et al. (Frontiers in Psychiatry, 2018)
Gambling disorder is a psychiatric condition that was recently recategorized as a non-substance-related addiction in the Diagnostic and Statistical Manual of Mental Health Disorders. Criminal activity is commonly associated with gambling; however, few empirical studies to date have examined sociodemographic and psychological variables in this population. In this study, we explored criminal behavior history in a sample of consecutively recruited treatment-seeking gamblers (n = 382) and compared subjects with a history of illegal acts (n = 103, 26.9%) to those with no criminal record (n = 279, 73.1%). Impulsivity and personality traits were specifically explored, along with other gambling-related severity factors. We found that gamblers who engaged in illegal activity were more likely to endorse high levels of urgency (i.e. the tendency to act out when experiencing heightened emotional states) and increased lack of premeditation. Gamblers with a history of criminal behavior also had greater gambling disorder severity levels and gambling-related debts. Additionally, these gamblers reported lower levels of self-directedness, which is characterized by difficulty in establishing and redirecting behavior towards one’s goals. Likewise, gamblers who had conducted criminal acts showed a tendency to engage in greater risk-taking behavior. These results shed new light on this understudied population and provide insights for developing targeted harm-prevention interventions and treatment protocols.